Characterizing Bone Mineral Density Using Lumbar Spine Computed Tomography Attenuation in Patients With Distal Radius Fractures - Ward, Christina M. (Geriatr Orthop Surg Rehabil, 2019)
INTRODUCTION: This study examines how many patients with distal radius fracture (DRF) eligible for bone health evaluation could potentially be screened using bone mineral density (BMD) estimation by L1 vertebra computed tomography (CT) attenuation obtained for other purposes. MATERIALS AND METHODS: For all adult patients with DRF who presented over a 5-year period, we recorded the age, sex, dual-energy X-ray absorptiometry (DXA) results up to 3 years prior to injury or 1 year post-injury, and L1 CT attenuation on any CT including L1 that had been performed within 6 months of their fracture.(1) We compared the availability of L1 CT attenuation measurement to the rate of DXA scan use. We calculated the percentage of patients with osteoporosis and compared attenuation results to DXA results in those patients where both tests were available. RESULTS: Of 1853 patients with DRF, an L1 CT had been obtained in 195 patients. Of the 685 patients who met criteria for osteoporosis screening, 253 (37%) patients had undergone only DXA screening, 68 (10%) patients had an L1 CT only, and 18 (2%) patients had both tests. Of the 86 patients who met criteria for osteoporosis screening and had an adequate CT, 67 (78%) demonstrated L1 attenuation <135 HU, and 79 (92%) had CT attenuation <160 HU. DISCUSSION: Our study found that 10% of patients with a distal radius fracture who met the criteria for osteoporosis screening had a CT scan that could be used to estimate bone density and that the majority of those patients met criteria for osteoporosis based on CT attenuation. CONCLUSIONS: Utilization of opportunistic BMD screening with L1 CT attenuation offers the potential to increase osteoporosis screening from 40% to 50% of eligible patients and make the diagnosis of osteoporosis in an additional 8% of patients with DRF at no additional cost.